Anesthesia Management of Pediatric Victims After the February 6, 2023, Kahramanmaraş Earthquake at a Third-Level Hospital - Ozmert, Sengul; Isiktekin, Melike Demir; Taygurt, Tugba Nur; Civelek, Sema; Bayir, Tuba; Bayar, Rabia; Yasar, Niyazi Erdem (Wiley, 2025)
Introduction Earthquakes are chaotic events that cause severe physical and psychological devastation. Due to their anatomical and physiological differences and fragile nature, pediatric earthquake survivors require special attention in anesthesia management. This retrospective study aims to share our experiences and anesthesia techniques applied to pediatric earthquake victims in our tertiary care pediatric hospital. Furthermore, the study aimed to determine the time spent under rubble cutoff value for the development of crush syndrome and creatine kinase cutoff value for the development of acute kidney injury in child earthquake victims.Methods Child earthquake victims under the age of 18 who underwent anesthesia in our hospital after the earthquake that occurred on February 6, 2023, were included in this study. Demographic data, Glasgow Coma Scale scores at admission, the time spent under rubble, existing injuries, Injury Severity Score, presence of crush syndrome and acute kidney injury, need for hemodialysis, length of hospital and intensive care unit stay, type of surgical intervention, and preoperative and discharge laboratory results were analyzed. The type of anesthetic agents used and airway management techniques were recorded.Results A total of 45 pediatric earthquake victims underwent 362 surgical interventions. Extremity injuries were more common in our patients. We most frequently administered the MAC technique to our patients using sedation and ketamine-based general anesthesia. For airway management, nasal O2 support (44.0%) and SGA (43.2%) were most commonly used. The mean Injury Severity Score was calculated as 22.18 (95% CI: 19.17-25.18). We found that a cutoff value of >= 22.5 min spent under debris strongly predicted the development of crush syndrome, and a creatine kinase cutoff value of >= 32 029 IU/L strongly predicted the development of AKI.Conclusion The findings of our study may serve as a guide for anesthesia management and perioperative processes in pediatric earthquake victims in future disaster scenarios.Trial Registration ClinicalTrials.gov identifier: NCT06310265
Keywords: anesthesia; crush injury; earthquake; pediatric